Short-term effects of 448 kilohertz radiofrequency stimulation on supraspinatus tendon elasticity measured by quantitative ultrasound elastography in professional badminton players: a double-blinded randomized clinical trial - Navarro-Ledesma, S.; Gonzalez-Muñoz, A. (International Journal of Hyperthermia, 2021)
Objective: To study changes in supraspinatus tendon elasticity after a 448 kHz capacitive resistive monopolar radiofrequency (CRMR) intervention in professional badminton players. Design: Double-blinded randomized clinical trial. Setting: All participants were recruited in a private care practice. Participants were randomized to receive either a CRMR treatment (n=19) or placebo (n=19). Subjects: Professional badminton players (n=38). Intervention: A total of nine intervention (three per week) with CRMR at 448 kHz were carried out in the experimental group. The same intervention without an active CRMR current was carried out in the control group. Main measures: Mean values of three different regions of the supraspinatus tendon were reported at baseline (T1), immediately after the intervention (T2) and one week after the end of the whole intervention program (T3) using quantitative ultrasound strain elastography (SEL). Results: There were statistically significant differences in the supraspinatus tendon elasticity immediately after the intervention (p=<.001) and one week after the end of the whole intervention program (p=.001). Conclusion: CRMR at 448 kHz produces significant changes in supraspinatus tendon elasticity after an intervention program of three weeks and those changes last for a week when compared to control group.